NATO attack on FR Yugoslavia in 1999 was used to test the effectiveness of new weapons - Anđelković-Lukić, Mirjana N.; Radović, Ljubica M. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: During the 1999 NATO attack on Yugoslavia, three new weapons were used and tested for the first time. The first is the strategically invisible B-2 bomber, the second is the new JDAM (Joint Direct Attack Ammunition) and the third is the "soft bomb", or the blackout bomb, made of thin electrically conductive fibers. The aim of the paper is to present the new combat devices used during the aggression on the FRY and to quantitatively detect the elements of electrically conductive fibers. The paper also presents the lawsuit of the Federative Republic of Yugoslavia (FRY) to the International Criminal Tribunal for the former Yugoslavia (ICTY) in The Hague. The lawsuit was rejected. Methods: Physical and chemical analyzes of the fibers were performed. An electron microscope, SEM JSM Jeol 6610LV, was used to analyze the physicochemical characteristics of electrically conductive fibers. It provides the information on the morphology of the sample surface, resulting in a high-resolution image.The microscope is equipped with an X-ray detector (Oxford Instrumets X-Max 20 mm2) for EDS analysis (Energy Dispersive Spectroscopy). It enables the determination of the chemical composition of the material in the analyzed sample volume, based on the interaction between the directed electron beam and the sample atom. Results: The characteristics of the B-2 stealth aircraft used to bomb the FRY are shown. The JDAM bomb is an improved ordinary MK bomb with electronic devices added to guide the bomb via satellites. A semi-quantitative analysis of the fibers was performed on the SEM, confirming that the metal layer of the fiber predominantly consists of aluminum, and the non-metallic layer has the highest proportion of silicon dioxide. The fiber is carcinogenic. Conclusion: In 1999, the territory of Yugoslavia was a testing ground for new combat weapons of NATO aviation - B-2 and JDAM guided bombs. Blackout bombs were dropped on the electrical power systems of Yugoslavia leaving the whole Serbia without electricity for hours. Not only was the bombing-caused environmental pollution radiological and chemical but it was also caused by glass-aluminum electrically conductive fibers as pollutants.